2010
DOI: 10.4049/jimmunol.1000164
|View full text |Cite
|
Sign up to set email alerts
|

Partial Redundancy of the Pattern Recognition Receptors, Scavenger Receptors, and C-Type Lectins for the Long-Term Control of Mycobacteriumtuberculosis Infection

Abstract: Mycobacterium tuberculosis is recognized by multiple pattern recognition receptors involved in innate immune defense, but their direct role in tuberculosis pathogenesis remains unknown. Beyond TLRs, scavenger receptors (SRs) and C-type lectins may play a crucial role in the sensing and signaling of pathogen motifs, as well as contribute to M. tuberculosis immune evasion. In this study, we addressed the relative role and potential redundancy of these receptors in the host response and resistance to M. tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 64 publications
5
70
0
2
Order By: Relevance
“…tuberculosis and all other species of mycobacteria, many of which are opportunistic intracellular pathogens, owe much of their resilience to a distinctive lipid-rich cell envelope that not only protects the cells against harsh environments but also contains many molecules that are immune effectors crucial in evading the host immune response (Briken et al, 2004;Ishikawa et al, 2009;Schafer et al, 2009;Court et al, 2010;Ehlers, 2010;Philips and Ernst, 2012;Lang, 2013;Nobre et al, 2014). Besides glycolipids and glucans that constitute most of the M. tuberculosis cell envelope, several secreted proteins have been identified and shown to also play fundamental roles in M. tuberculosis survival and proliferation within the host (Abdallah et al, 2007;Philips, 2008;Philips and Ernst, 2012).…”
Section: Mycobacterium Tuberculosis: Biology and Infectionmentioning
confidence: 99%
“…tuberculosis and all other species of mycobacteria, many of which are opportunistic intracellular pathogens, owe much of their resilience to a distinctive lipid-rich cell envelope that not only protects the cells against harsh environments but also contains many molecules that are immune effectors crucial in evading the host immune response (Briken et al, 2004;Ishikawa et al, 2009;Schafer et al, 2009;Court et al, 2010;Ehlers, 2010;Philips and Ernst, 2012;Lang, 2013;Nobre et al, 2014). Besides glycolipids and glucans that constitute most of the M. tuberculosis cell envelope, several secreted proteins have been identified and shown to also play fundamental roles in M. tuberculosis survival and proliferation within the host (Abdallah et al, 2007;Philips, 2008;Philips and Ernst, 2012).…”
Section: Mycobacterium Tuberculosis: Biology and Infectionmentioning
confidence: 99%
“…Recent in vivo infection studies, however, have shown that neither MARCO nor Mincle is required for control of M. tuberculosis infection in the mouse model (51,52), suggesting that there are redundant pathways through which M. tuberculosis stimulates the host immune response. Upregulation of several cytokines (TNF-␣, IL-1␤, and IL-10) and chemokines (CCL3, CCL4, CCL7, CCL12, CXCL1, CXCL2, and CXCL10) important in the response to TB at least partially explains the ability of TDM to induce many of the lesions and symptoms observed during TB (4,5,(53)(54)(55)(56)(57)(58).…”
Section: Figmentioning
confidence: 99%
“…With respect to SR-A, this receptor can also bound TDM, nevertheless, this recognition diminishes TNF-/MIP-1-production by activated macrophages, suggesting that SR-A have an important role in the suppression of the excessive inflammatory response presented during mycobacterial infection (Ozeki et al, 2006). Recent evidence suggest that scavenger receptors along with C-type lectins, cooperate to maintain controlled the immune response established in vivo against the mycobacterial infection (Court et al, 2010).…”
Section: Scavenger Receptorsmentioning
confidence: 99%